Examining New Media Consumption from the standpoint of OTT Streaming Services - Rajarathi Karunakaran; Selvabaskar S; Karthik Ram M; Guhan R (Petra International Journal of Business Studies, 2023)
The study deals with consumer behavior in consuming OTT media streaming services in India. Nine variables of motivations such as Relaxation, Companionship, Habit, Pastime, Entertainment, Social interaction, Information, Arousal, and Escape are studied, which affect the intention to continue to subscribe to these services. Tools such as frequency analysis, One Way ANOVA, and Regression analysis are used to study the demographic characteristics, levels of motivation, differences between the demographic factors and variables of motivation, and the effect of variables of motivation on intention to continue subscription studied, respectively. The sample size was 309. Entertainment was the variable with the highest level of motivation. Except for Entertainment and Escape, all the variables significantly differed in different demographic groups concerning Gender, Age, and Education. Relaxation, Companionship, Habit, Information sharing, and Escape have been found to have a significant relationship with the intention to continue the subscription.